Exploiting epoxy-rich poly(ethylene glycol) films for highly selective ssDNA sensing via electrochemical impedance spectroscopy - Zhao, Zhiyong; Zharnikov, Michael (Physical chemistry, chemical physics, 2023)
This study introduces an alternative approach to immobilize thiolated single-stranded DNA (ssDNA) for the DNA sensing. In contrast to the standard, monomolecular assembly of such moieties on gold substrate, over the thiolate-gold anchors, we propose to use bioinert, porous polyethylene glycol (PEG) films as a 3D template for ssDNA immobilization. The latter process relies on the reaction between the thiol group of the respectively decorated ssDNA and the epoxy groups in the epoxy-rich PEG matrix. The immobilization process and subsequent hybridization ability of the resulting sensing assembly were monitored using cyclic voltammetry and electrochemical impedance spectroscopy, with the latter tool proving itself as the most suitable transduction technique. Electrochemical data confirmed the successful immobilization of thiol-decorated ssDNA probes into the PEG matrix over the thiol-epoxy linkage as well as high hybridization efficiency, selectivity, and sensitivity of the resulting DNA sensor. Whereas this sensor was equivalent to the direct ssDNA assembly in terms of the efficiency, it exhibited a better selectivity and bioinert properties in view of the bioinert character of the PEG matrix. The above findings place PEG films as a promising platform for highly selective ssDNA sensing, leveraging their flexible chemistry, 3D character, and bioinert properties.